FREQUENCIES OF GAS OSCILLATIONS CAUSED BY THE COMBUSTION OF SOLID FUEL IN COAXIAL TUBES - E. V. Semenova; O. V. Iovleva; I. V. Larionova; Y. V. Vankov (Известия высших учебных заведений: Проблемы энергетики)
Organization of pulsating combustion mode is one of the possible solutions to improve energy efficiency installations tasks that use hydrocarbon fuels. For stratified combustion of solid fuels, especially solid waste technogenic promising are coaxial system, allowing to provide secondary air flow to the combustion zone. In this paper, an analysis of its own oscillations of gas in coaxial pipes system. The effect of the mutual arrangement of the combustion chamber and the resonance frequency of the pipe on the gas fluctuations.